Too little Destruction too little Creation A Schumpeterian Diagnosis of Barriers to Sustained Growth in Ukraine - Gianella, Christian (OECD Publishing, 2007)
This paper examines problems of entry, exit and competition in Ukrainian product markets. It finds that Ukraine still has too little of all three, and that exit mechanisms, in particular, function poorly. Since impediments to entry and exit are largely the product of excessive and ill administered regulation, the paper also provides a systematic assessment of product-market regulation in Ukraine, using indicators developed by the OECD Economics Department. Finally, the paper presents the main findings of two empirical studies concerned with the potentially large benefits of opening up markets, via both increased competition and further privatisation, for productivity growth in Ukraine. This paper relates to the 2007 Economic Survey of Ukraine (www.oecd.org/eco/studies/ukraine)
Keywords: Economics; Ukraine